Digital Marketing Strategies to Build Customer Loyalty: A Systematic Review of Sustainable Financial Benefits - Rahayu, Sri (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study examines the role of integrated digital marketing strategies, including personalized content, Customer Relationship Management (CRM) systems, and social media marketing, in building customer loyalty and driving long-term financial benefits. The research design uses a systematic literature review to examine how these digital tools work together to improve things. This is based on theories like relationship marketing and the resource-based view (RBV). The findings demonstrate that integrating these strategies leads to more muscular customer retention, reduced customer acquisition costs, and enhanced return on investment (ROI). Additionally, it confirms that a multi-channel approach, which aligns CRM data with personalized content and social media, provides a more cohesive customer experience, leading to increased customer lifetime value (LTV). The study highlights practical implications for businesses, emphasizing the need for integrated digital strategies to enhance customer engagement and financial sustainability. However, the study's limitations include its reliance on secondary data and the exclusion of emerging technologies like artificial intelligence. Future research should focus on longitudinal studies and explore industry-specific case studies to provide more tailored insights into the evolving landscape of digital marketing.